Accuracy of the ABC/2 Score for Intracerebral Hemorrhage: Systematic Review and Analysis of MISTIE, CLEAR-IVH, and CLEAR III. Issue 9 (September 2015) - Webb, Alastair J.S.; Ullman, Natalie L.; Morgan, Tim C.; Muschelli, John; Kornbluth, Joshua; Awad, Issam A.; Mayo, Stephen; Rosenblum, Michael; Ziai, Wendy; Zuccarrello, Mario; Aldrich, Francois; John, Sayona; et al.
Abstract : Background and Purpose—: The ABC/2 score estimates intracerebral hemorrhage (ICH) volume, yet validations have been limited by small samples and inappropriate outcome measures. We determined accuracy of the ABC/2 score calculated at a specialized reading center (RC-ABC) or local site (site-ABC) versus the reference-standard computed tomography–based planimetry (CTP). Methods—: In Minimally Invasive Surgery Plus Recombinant Tissue-Type Plasminogen Activator for Intracerebral Hemorrhage Evacuation-II (MISTIE-II), Clot Lysis Evaluation of Accelerated Resolution of Intraventricular Hemorrhage (CLEAR-IVH) and CLEAR-III trials. ICH volume was prospectively calculated by CTP, RC-ABC, and site-ABC. Agreement between CTP and ABC/2 was defined as an absolute difference up to 5 mL and relative difference within 20%. Determinants of ABC/2 accuracy were assessed by logistic regression. Results—: In 4369 scans from 507 patients, CTP was more strongly correlated with RC-ABC ( r 2 =0.93) than with site-ABC ( r 2 =0.87). Although RC-ABC overestimated CTP-based volume on average (RC-ABC, 15.2 cm 3 ; CTP, 12.7 cm3), agreement was reasonable when categorized into mild, moderate, and severe ICH (κ=0.75; P <0.001). This was consistent with overestimation of ICH volume in 6 of 8 previous studies. Agreement with CTP was greater for RC-ABC (84% within 5 mL; 48% of scans within 20%) than for site-ABC (81% within 5 mL; 41% within 20%). RC-ABC had moderate accuracy for detecting ≥5 mL change in CTP volume between consecutive scans (sensitivity, 0.76; specificity, 0.86) and was more accurate with smaller ICH, thalamic hemorrhage, and homogeneous clots. Conclusions—: ABC/2 scores at local or central sites are sufficiently accurate to categorize ICH volume and assess eligibility for the CLEAR-III and MISTIE III studies and moderately accurate for change in ICH volume. However, accuracy decreases with large, irregular, or lobar clots. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: MISTIE-II NCT00224770; CLEAR-III NCT00784134. Abstract : Supplemental Digital Content is available in the text.